2021
DOI: 10.1002/agj2.20883
|View full text |Cite
|
Sign up to set email alerts
|

Late‐season N fertilization effects on soybean seed protein and biological N2 fixation

Abstract: Soybean [Glycine max (L.) Merr.] seed protein concentration has been declining over the past decades with protein values falling below the ∼40% (dry weight base) required for optimal industrial processing. Further refinement of management practices is needed to help maintain concentrations above market standards. The objective of this work was to evaluate the impact of N fertilization during late reproductive stage on soybean seed protein on two cultivars differing in seed protein concentration in order to unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Lastly, seed and meal protein concentration showed the largest percentage of variability associated to random factors and to unaccounted sources of variation in our analysis ( Figure 2 ). Low repeatability in seed protein concentration is consistent with results by Dardanelli et al (2006) and suggests that other site-specific factors may be driving variation in seed and meal protein concentrations, such as soil fertility and management practices that affect crop N availability ( Bosaz et al, 2021 ; Chiluwal et al, 2021 ). However, we did find some significant effects and clear trends that provide new understanding on the interactive effect of planting date and cultivar maturity that can help increase oil yield and manage risk of deficient meal protein concentration.…”
Section: Discussionsupporting
confidence: 63%
“…Lastly, seed and meal protein concentration showed the largest percentage of variability associated to random factors and to unaccounted sources of variation in our analysis ( Figure 2 ). Low repeatability in seed protein concentration is consistent with results by Dardanelli et al (2006) and suggests that other site-specific factors may be driving variation in seed and meal protein concentrations, such as soil fertility and management practices that affect crop N availability ( Bosaz et al, 2021 ; Chiluwal et al, 2021 ). However, we did find some significant effects and clear trends that provide new understanding on the interactive effect of planting date and cultivar maturity that can help increase oil yield and manage risk of deficient meal protein concentration.…”
Section: Discussionsupporting
confidence: 63%
“…These contrasting results could be attributed to the moment in which the crop was fertilized and the rates, but Bosaz et al. (2021) also showed no yield improvements even with late N applications when BNF is declining.…”
Section: Discussionmentioning
confidence: 99%
“…These contradictory results might be associated with these studies not being specifically designed to test sowing date effects without other confounding factors that are common when sowing date is a covariable associated to a location. In a field experiment, where sowing date was purposely manipulated, Bosaz et al (2021) showed BNF was reduced in 6% (from 52.4 to 46.6% in early and late sowing dates, respectively) when the sowing was delayed by 33 d (an average decline of 0.15% d −1 ). This result, from a narrow sowing window of 54 d, is consistent with our results showing declines in the percentage of the total canopy N uptake that is coming from BNF across years, genotypes, and N fertilization levels, at an average rate of 0.22% d −1 when delaying the sowing date from mid-September to mid-December.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations